2015
DOI: 10.1186/s12935-015-0241-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting colorectal cancer stem cells using curcumin and curcumin analogues: insights into the mechanism of the therapeutic efficacy

Abstract: Colorectal cancer is one of the commonest cancers in the world and it is also a common cause of cancer-related death worldwide. Despite advanced treatment strategies, the disease is rarely cured completely due to recurrence. Evidence shows that this is due to a small population of cells, called cancer stem cells (CSCs), in the tumour mass that have the self-renewal and differentiation potential to give rise to a new tumour population. Many pre-clinical and clinical studies have used curcumin and its analogues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 109 publications
(113 reference statements)
0
65
0
Order By: Relevance
“…These facts emphasize that curcumin can act as a chemosensitizer which makes CSCs now sensitive toward anticancer therapy. Therefore, treatment with a combination of an anticancer agent along with curcumin could be much more effective than that with anti-cancer agent alone 86. This potential treatment modality using curcumin as an adjuvant can be further developed by utilizing more effective drug-delivery system like nano molecules, which can open a new avenue to prevent cancer and its relapse.…”
Section: Curcumin and Novel Treatment In Csc Sensitizationmentioning
confidence: 99%
“…These facts emphasize that curcumin can act as a chemosensitizer which makes CSCs now sensitive toward anticancer therapy. Therefore, treatment with a combination of an anticancer agent along with curcumin could be much more effective than that with anti-cancer agent alone 86. This potential treatment modality using curcumin as an adjuvant can be further developed by utilizing more effective drug-delivery system like nano molecules, which can open a new avenue to prevent cancer and its relapse.…”
Section: Curcumin and Novel Treatment In Csc Sensitizationmentioning
confidence: 99%
“…The results vary among studies: according to currently available data, while most studies showed a correlation between Hh and CRC (98 out of 101 studies), there are three researches that claimed that Hh is not, or at least not directly, related to CRC 2527. Within the 98 studies, 92 studies confirmed upregulation effects and 5 revealed downregulation effects of the Hh pathway in CRC 435,40,42,4749,53113. Moreover, among the studies in favor of a Hh-CRC correlation, its exact function in the formation, proliferation, drug resistance, and metastasis of CRC is not uniform.…”
Section: Hh Signaling Pathwaymentioning
confidence: 99%
“…8; In relation to the unifying mechanistic approach, metabolism may yield a catechol type which lead to o-quinone or p-quinone structures, followed by ROS-OS (Kovacic & Somanathan, 2015). Study reveals cucrcumin ( Figure 1) induced caspase-3-mediated cleavage of β-catenin, leading to inactivation of Wnt/β-catenin signaling in intestinal, gastric, and colon cancer cells (Park, Hahm, Park et al, 2005;Jaiswal, Marlow, Gupta, & Narayan, 2002;Ramasamy, Ayob, Myint et al, 2015). Curcumin was also shown to attenuate the Wnt/β-catenin pathway through down-regulation of the transcriptional coactivator p300 (Ryu, Cho, & Song, 2008).…”
Section: Curcuminmentioning
confidence: 99%